Yinzhihuang injection induces apoptosis and suppresses tumor growth in acute myeloid leukemia cells. - Zhe Huang; Yunfu Shen; Xianming Fan; Qulian Guo; Wenzhe Ma (PLoS ONE)
Background The unmet needs in treating acute myeloid leukemia(AML) promote us to look for more effective and less toxic therapies. In this study, we discovered that Yinzhihuang injection(YZHI), a traditional Chinese patent medicine for hepatitis treatment, suppressed the growth of AML cells. Method Anti-proliferative activities of YZHI were measured by CCK-8 assay. Cell cycle arrest was evaluated by PI staining, and apoptosis was evaluated by annexin V/PI staining. To explore the cell cycle arrest and cell death mechanism induced by YZHI, we assessed a series of assays, including measurements of the protein expression and cellular ATP. The anti-tumor activity was further demonstrated in nude mice. Results Flow cytometric and biochemical analysis revealed that YZHI caused cell cycle arrest and induced apoptosis in the AML HL-60 cells. Mechanistically, YZHI activated AMPK by promoting phosphorylation of the kinase. The active AMPK negatively regulated the downstream target mTORC1, leading to the inhibition of cell proliferation and induction of apoptosis. Pretreatment with the AMPK inhibitor compound C rescued YZHI induced apoptosis and partially restored cell proliferation of HL-60. Consistent with the data in vitro, YZHI obviously suppressed subcutaneous xenograft growth in nude mice. Conclusions In a word, our data suggest that YZHI can be repurposed for the treatment of AML, which is worthy of further clinical evaluation.